Հյուսիսային Գողթնի միջբարբառը Նախիջևանի բարբառային համապատկերում - Վարդանյան, Արտակ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В канун событий 1918–1920 гг., когда большинство населения составляли армяне, территория Нахиджевана охватывала около семи десятков армянонаселенных городов и сел. Преобладающая часть населения говорила на диалектах переселенцев, обосновавшихся на территории с 1828 года – хойском диалекте (33 поселения) и на марагинском диалекте (3 поселения). Сохранились также местные диалекты – агулисский (7 поселений), джугинский (1 поселение), араратский (4 поселения), арцах-сюникский (7 поселений), джаук-вайкский (2 поселения), говоры Северного Гохтна (6 поселений). Вследствие внутренних перемещений населения образовались также межговоры – джульфинский (джугинский-хойский), ордубадский (агулисский-хойский). On the eve of the events of 1918–1920, when the majority of the population were Armenians, the territory of Nakhijevan covered about seven dozen Armenian-settlements cities and villages. The overwhelming majority of the population spoke the dialects of the settlers who had settled in the territory since 1828 – the Khoy dialect (33 settlements), as well as the Maragha dialect (3 settlements). Local dialects have also survived – the Agulis dialect (7 settlements), the Jugha dialect (1 settlement), the Ararat dialect (4 settlements), the Artsakh-Syunik dialect (7 settlements), the Jahuk-Vayk interdialect (2 settlements), the subdialects of North Goghtn (6 settlements). As a result of internal displacements of the population, inter-subdialects were also formed – Julfa (JughaKhoy), Ordubad (Agulis-Khoy).
Keywords: Philology; Linguistics